Local Chorographies and Structures of Composite Monarchy in the Early Modern Antiquarian Discourse - Palamarchuk, Anastasia («Քոփի Փրինթ» տպագրատուն)
The concept of the composite monarchy, developed in contemporary historiography, is an effective analytical research tool for studying large territorial states with complex internal structure. The ground of this concept lies in the famous works by H.G. Koenigsberger [20:301-333;21,19] and J.H. Elliott [11:47-71;12]. Each of them (Koenigsberger mostly relying on the continental material, Elliott - primarily on the British one) reflected the fact that the vast majority of the early Modern States had complex and elaborate internal structure not only in the administrative aspect, but also in the territorial one. In such complex polities the royal power not only evolved from suzerainty to sovereignty, but it also expanded upon a number of autonomous or semi-autonomous territorial entities - composites. The definition of composite comprised autonomies marked by the high level of admin-istrative subjectivity, and the process of their incorporation (implemented or potential) was perceived primarily in formal legal aspect. Կոմպոզիտար միապետության հայեցակարգը, որը մշակվել է ժամանակակից պատմագրության մեջ, արդյունավետ վերլուծական հետազոտական գործիք է բարդ ներքին կառուցվածքով խոշոր տարածքային պետությունների ուսումնասիրության համար: Այս հայեցակարգի հիմքն են հանդիսանում հայտնի հետազոտողների` Քյոնիգսբերգերի և Էլիոթի աշխատությունները: Նրանցից յուրաքանչյուրը (Քյոնիգսբերգերը հիմնականում հենվում է մայրցամաքային նյութի վրա, Էլիոթը՝ բրիտանականի) արտացոլում էր այն փաստը, որ վաղ ժամանակակից նահանգների ճնշող մեծամասնությունն ուներ բարդ և մշակված ներքին կառուցվածք ոչ միայն վարչական առումով, այլ նաև տարածքային: Նման բարդ քաղաքականության ժամանակ թագավորական իշխանությունը ոչ միայն զարգացավ գերիշխանությունից դեպի ինքնիշխանություն, այլև ընդլայնվեց մի շարք ինքնավար կամ կիսաինքնավար տարածքային միավորների՝ կոմպոզիտների:
Keywords: Politics; Structure of states